Mapování lymfatik v axile jako možnost prevence lymfedému u pacientek s karcinomem prsu - první výsledky anatomické studie - Pavlista, D; Eliška, O (Ceska gynekologie, 2012)
OBJECTIVE: Lymphatic mapping is a method to find and preserve upper extremity lymphatics during axillary surgery (axilla clearance and sentinel node biopsy) in breast cancer patients. This may reduce the incidence of lymphedema. We examined on anatomical model, if the lymphatic drainage of the upper extremity is fully separable from the lymphatic drainage of the breast. We further endeavored to find an explanation as to why lymphedema occurs in the upper extremity after sentinel node biopsy in breast carcinoma. DESIGN: Pilot study. SETTING: Oncogynecologic Center, Department of Obstetrics and Gynecology, First Faculty of Medicine, Charles University in Prague and General University Hospital, Prague. METHODS: Patent blue dye was injected deep and superficially in arm and breast bilaterally in 9 cadavers. After visualization and precise dissection of the lymphatic vessels and nodes, a record of their routes was made. A scheme of arm and breast lymphatics was constructed. RESULTS: The lymph from arm is drained by 2-4 main afferent collectors. As opposed to cranial and medial collectors, caudal collectors diverged from the axillary vein and entered the caudal axilla. In one case the caudal collector entered a node, which was considered to be the sentinel node of the breast. The other important finding is the demonstration of lymphatic anastomoses that take place between imaged nodes in the caudal axilla, which is the most frequent localization of the breast sentinel lymph node. CONCLUSION: The relationship of lymphatic drainage of the arm and breast are closely related and share connections. These connections represent the main problem, which could explain lymphedema following surgery if damaged. Further studies are necessary to improve understanding of this method and to increase the number of observations.
Keywords: Humans; Arm; Female; Aged; Breast; senioři; lidé; Lymph Node Excision; lymfedém; rosanilinová barviva; Rosaniline Dyes; biopsie sentinelové lymfatické uzliny; Lymphatic Vessels; Breast Neoplasms; Lymph Nodes; lymfatické uzliny; ženské pohlaví; Sentinel Lymph Node Biopsy; Lymphedema; nádory prsu; lymfadenektomie; Axilla; axila; paže; lymfatické cévy; prsy